PEMBUATAN MATERIAL KOMPOSIT BERBAHAN DASAR SABUT KELAPA DAN JERAMI PADI SEBAGAI PEREDAM KEBISINGAN - Auliana Diah Wilujeng; Laily Ulfiyah; Annafiyah Annafiyah; Muhammad Helmi Taqiuddin (Jurnal Technopreneur (JTech), 2022)
Noise is an environmental problem that needs to be addressed because it not only disturbs comfort but also causes hearing health problems. One of the ways to deal with noise is by installing sound absorbing materials. Sound absorbers commonly used are rockwool or glasswool. However, these materials are quite expensive. Therefore, various types of sound absorbing materials that are cheap and environmentally friendly, namely coconut coir and rice straw. The material made is a circle with a diameter of 100 mm and a thickness of 10 mm. The variation used is the ratio of the quantity of coconut coir and rice straw with gypsum. The variations of the coconut coir and rice straw materials used are 15 grams, 25 grams, and 35 grams. Meanwhile, 400 mL of gypsum is used. Both materials were tested to obtain the sound attenuation coefficient value. The best results obtained from the test are a mixture of coconut coir and gypsum with a sound attenuation coefficient of 0.45.